Cerebral venous thrombosis: report of 2 cases of hemorrhagic venous infarction - Hoang, Thi Phuong Thao (Radiol Case Rep, 2020)
Cerebral venous thrombosis (CVT), a rare but potentially severe cerebrovascular disease, is defined as the thrombosis of a cortical or deep cerebral vein, or a cerebral venous sinus. This article reports 2 cases of CVT. In the first case, the patient is a 40-year-old woman with a history of 2 miscarriages, using oral contraception and presenting intense headache, cervical irradiation, and drowsiness. The second case reports a 43-year-old woman with a history of Crohn disease and daily use of oral contraception, presenting headache, neck pain, and hypersensitivity to noise and light. Noncontrast CT, CT venography, magnetic resonance imaging (MRI) and MR venography (MRV), first-line noninvasive diagnostic modalities in clinical practice, led us to the diagnosis of CVT: hypoplastic lateral sinus CVT in the first case and deep cerebral vein CVT complicated by hemorrhagic infarction in the second case. The early diagnosis of CVT is extremely important, but often a challenge due to highly variable clinical presentation and radiographic findings. MRI and the MRV play a crucial role in case of anatomical variant and in better assessing the extension of thrombus, as well as parenchyma involvement and complications.